2017
DOI: 10.1016/j.apjtm.2017.01.018
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare workers' knowledge towards Zika virus infection in Indonesia: A survey in Aceh

Abstract: The knowledge of the doctors in Aceh regarding Zika infection is relatively low. Doctors who have a good knowledge on Zika infection are more confident to established Zika disease as differential diagnosis in their clinical setting. Therefore, such program to increase healthcare providers' knowledge regarding Zika infection is needed to screen potential carriers of Zika infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
58
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 42 publications
(72 citation statements)
references
References 26 publications
11
58
2
Order By: Relevance
“…This finding is similar with the reports of previous studies even though they assessed only the Physicians or Dental practitioners [24,25]. Unhealthy information seeking behaviour or neglect among health workers may explain their poor knowledge of ZIKV infection as found this study.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…This finding is similar with the reports of previous studies even though they assessed only the Physicians or Dental practitioners [24,25]. Unhealthy information seeking behaviour or neglect among health workers may explain their poor knowledge of ZIKV infection as found this study.…”
Section: Discussionsupporting
confidence: 83%
“…Additionally, we found that HCPs who are in academia or those that practice in government-owned health facilities had better knowledge compared to those that are self-employed or work in private hospitals and clinics. Surprisingly, a contrary finding was reported in a study conducted in Indonesia, where the authors observed that Physicians in private hospitals had a higher odd of having good knowledge of ZIKV infection compared to those that work in government hospitals [24]. Since most people in Nigeria prefer accessing medical care in government hospitals because it's less expensive and most often have qualified and competent HCPs compared to the private hospital.…”
Section: Discussioncontrasting
confidence: 44%
“…answered three and two questions correctly, respectively). We have used a similar cut-off point to dichotomize variables in previous studies (Harapan et al, 2017a;Harapan et al, 2018a;Harapan et al, 2017b;Harapan et al, 2016;Harapan et al, 2019). A two-step logistic regression analysis was used to explore the potential explanatory variables associated with confidence.…”
Section: Discussionmentioning
confidence: 99%
“…Following the design and setting of previous studies (Harapan et al, 2017a;Harapan et al, 2018a;Harapan et al, 2019), an online cross-sectional study was conducted in Indonesia between 25 May 2019 and 25 July 2019. The population was all registered GPs.…”
Section: Study Design Setting and Participantsmentioning
confidence: 99%
See 1 more Smart Citation